Religious and Spiritual Struggles Brief Inventory: Initial Validation and Psychometric Study - Juan González-Rivera; Yazmín Álvarez-Alatorre (Interacciones)
Background: Religious and spiritual struggles are psychological conflicts associated with a relationship with divinity or religious organizations' particular practices and teachings. These struggles can affect health and well-being, causing emotional distress and pain. Objective: The purpose of this study was to develop and validate a brief measure that examines religious and spiritual struggles (R/E) from the theoretical framework of Exline. Method: This research had an instrumental design. An availability sampling composed of 312 participants residing in Puerto Rico was used. Results: The psychometric analysis confirmed that the scale has a four-dimensional structure (divine struggles, interpersonal struggles, evil struggles, intrapersonal struggles), solid reliability, construct validity, and convergent validity. The 14 items met good discrimination values. Conclusions: These results suggest that the instrument can measure four types of R/E struggles in Puerto Rican adults. Furthermore, this new instrument will allow the advancement of new research on R/E struggles in Puerto Rico and Latin America.